2017
DOI: 10.1108/jbim-06-2016-0122
|View full text |Cite
|
Sign up to set email alerts
|

From websites to social media: exploring the adoption of internet marketing in emerging industrial markets

Abstract: Purpose This study aims to explore internet marketing adoption in emerging industrial markets across several internet-based technologies (i.e. social media platforms, static and transactional websites). Design/methodology/approach This study is mainly based on an exploratory research design and investigated the online presence of 570 industrial organizations in terms of their involvement in social media. This study also examines if websites are used for basic marketing communications (brochureware) or for co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
65
0
7

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(89 citation statements)
references
References 46 publications
2
65
0
7
Order By: Relevance
“…Research studies on digital marketing (Mathews et al, 2016) indicate that firms deploying Internet marketing capabilities will benefit due to the reduction of information uncertainty and increased capacity to develop international network capabilities. Shaltoni (2017) found that half of the investigated organizations are using the Internet as a one-way communication vehicle through static websites. He revealed that decision-makers in emerging industrial markets are enthusiastic about social media, particularly Facebook.…”
Section: Theoretical Aspects Of Digital Marketingmentioning
confidence: 99%
“…Research studies on digital marketing (Mathews et al, 2016) indicate that firms deploying Internet marketing capabilities will benefit due to the reduction of information uncertainty and increased capacity to develop international network capabilities. Shaltoni (2017) found that half of the investigated organizations are using the Internet as a one-way communication vehicle through static websites. He revealed that decision-makers in emerging industrial markets are enthusiastic about social media, particularly Facebook.…”
Section: Theoretical Aspects Of Digital Marketingmentioning
confidence: 99%
“…These two terms are similar but not synonyms. Even though Digital marketing is also known as Internet marketing, online marketing, web marketing or data-driven marketing [4], it is the umbrella term for a group of marketing processes that exploit all available digital channels and Internet technologies with the aim of promotion of branded products and services. Its development is a direct result of the increased electronic data, digital media usage and its impact in business sphere globally.…”
Section: Internet Marketing -Scope and Terminologymentioning
confidence: 99%
“…The second dilemma in online business is weather a company should have both social media business page and website, or just the first one. The importance of professional company's website is growing and it has become a standard in Internet marketing strategy, since it allow "better search engine marketing, full control of content and consequently better branding" [4].…”
Section: Limitations and Possible Risks Of Internet Marketingmentioning
confidence: 99%
“…Established in 2002 and unveiled the following year, LinkedIn is a networking platform primarily for linking up people for professional purposes (e.g. employment and business prospects) (Shaltoni, 2017). Peter, and Donnelly (2009) categories LinkedIn as a modern media networking site specifically designed to build professional networks.…”
Section: Modern Advertising Mediamentioning
confidence: 99%
“…Peter, and Donnelly (2009) categories LinkedIn as a modern media networking site specifically designed to build professional networks. Nowadays, firms utilise Twitter in order to directly connect with their clients and broadcast noteworthy information (Shaltoni, 2017). Twitter involves real-time information sharing through the so-called tweets and gives firms opportunities to go viral.…”
Section: Modern Advertising Mediamentioning
confidence: 99%